Enterococcus faecium WB2000 Inhibits Biofilm Formation by Oral Cariogenic Streptococci - Nao Suzuki; Masahiro Yoneda; Yuko Hatano; Tomoyuki Iwamoto; Yosuke Masuo; Takao Hirofuji (International Journal of Dentistry)
This study investigated the inhibitory effect of probiotic Enterococcus faecium WB2000 on biofilm formation by cariogenic streptococci. The ability of E. faecium WB2000 and JCM5804 and Enterococcus faecalis JCM5803 to inhibit biofilm formation by seven laboratory oral streptococcal strains and 13 clinical mutans streptococcal strains was assayed. The Enterococcal strains inhibited biofilm formation in dual cultures with the mutans streptococcal strains Streptococcus mutans Xc and Streptococcus sobrinus JCM5176 (P<0.05), but not with the noncariogenic streptococcal strains. Enterococcus faecium WB2000 inhibited biofilm formation by 90.0% (9/10) of the clinical S. mutans strains and 100% (3/3) of the clinical S. sobrinus strains. After culturing, the pH did not differ between single and dual cultures. The viable counts of floating mutans streptococci were lower in dual cultures with E. faecium WB2000 than in single cultures. Enterococcus faecium WB2000 acted as a probiotic bacterial inhibitor of cariogenic streptococcal biofilm formation.